Formação de professores de língua de sinais: um exemplo do projeto digit-libras - Oliveira, Everton Pessôa de (2021)
This thesis aims to investigate potential transformers in a proposal for a short course, for the training of sign language teachers, based on Social Activity as organizer of the curriculum. It is based on the Theory of Socio-Historical-Cultural Activity, considering the concepts of Curriculum and Decapsulation as theoretical contributions for analysis. This thesis is justified, because in the world context, the training of sign language teachers presents problems that run from the construction of the curriculum to the classes effectively taught. In addition, the deaf person's access to the educational context permeates teacher training. In this direction, the thesis proposes to teachers reflections focusing on a form of decapsulating teachinglearning, capable of encouraging students to act, in society, with greater freedom of expression. Methodologically, it is a Critical Collaboration Research, which analyzes the contradictions and collaboration as promoters of transformation of the subjects from the confrontation of ideas, in order to generate a new understanding of the contexts. The research context was the realization of a short teacher training course for the reevaluation of their practices in teaching sign language, reflecting on other possibilities related to the organization of the curriculum. The course, supported by a socio-historical-cultural view of language and teacher training, was planned, implemented and had its proposal analyzed in this thesis, to investigate potential transformers found in its realization. This process was evaluated by researchers from the LACE Research Group and members of the Digitmed Program, based at the Pontifical Catholic University of São Paulo. The research involved 12 subjects, assuming the following roles: a trainer-researcher, two tutors, eight deaf and hearing teachers, and a camera assistant. The course took place in two stages: the first, online; the second, in two face-to-face classes held at the Pontifical Catholic University of São Paulo. In the first stage, the data was produced through responses to a form on Google Forms and was intended to investigate among the participants the views of teacher training and language. In the second stage, through video recording during classes, seeking to offer theoretical contributions to reassess teachers' practices. The results indicate that the use of Social Activity as an organizer of the curriculum, supported by multi-courses can contribute for teachers to perceive the monological way in which the curricula of sign language courses are organized and reflect on the transformation of their teaching practices. Thus, visualizations about other ways to teach sign language can point to the need to train to reflect and transform